Le ricette della Lozana: cuoca, medichessa, estetista e fattucchiera. - PERUGINI, CARLA (Scripta)
In a short span of years, between the fifteenth and sixteenth centuries, in Italy as in Spain, cookbooks multiplied, codifying a canon that will remain so to our days, as well as the Antidotaries, with scientific or presumed remedies for the various diseases, primarily the French pox, and the books of secrets with advices on every domestic problem and on cosmetic treatments, as well as the handbooks available to those who wanted to use spells and predictions. Even in La Lozana andaluza recipes and advices of all kinds are wasted, but its author's irony and vis comica overwhelm the prescriptive and normative character of the genre, subverting both the language and the contents adopted by Francisco Delicado.